Conserving omnidirectional landscape connectivity under projected land-use change in Borneo - Katie L. Spencer; Nicolas J. Deere; Dave J.I. Seaman; Muhammad Aini; Namrata B. Anirudh; Ryan Avriandy; Gail Campbell-Smith; Susan M. Cheyne; Gabriella Fredriksson; Robithotul Huda; Joseph Hutabarat; Andrew J. Marshall; et al. (Biological Conservation, 2026)

Heterospecific social behavior in primates: insights into the evolutionary roots of pet-keeping - Cyril C. Grueter; Fany Roncin; K. Anne-Isola Nekaris; Jill Pruetz; Richard McFarland; Sabit Hasan; Malgorzata Arlet; Timothy M. Eppley; Susan M. Cheyne; Vincent Nijman; Eckhard W. Heymann; Pascal R. Marty; et al. (Primates, 2026)
Primate interspecific interactions with both other primates and non-primate species range from predator–prey dynamics to affiliative behaviors such as grooming, play, and carrying. While many primates participate in interspecific associations or commensal relationships, to our knowledge interspecific social interactions have never been systematically synthesized. Here, we present the first comprehensive review of such interactions, compiling 427 cases from the literature, media sources, and a global survey of primatologists. These involved 88 primate species and 127 non-primate species (including mammals, birds, reptiles, amphibians, malacostracans, and insects) across wild (n = 311) and captive (n = 111) contexts. The most frequent interactions occurred within or between primate families (e.g., Cercopithecidae–Cercopithecidae, Cebidae–Atelidae), though affiliative behaviors were also directed toward distantly related taxa such as dogs and birds. Play (n = 139) and grooming (n = 136) were most common. Juveniles and infants predominantly engaged in play, while adult females were more likely to groom. Adult males were less affiliative overall. Contrary to expectations, affiliative behaviors were not more often directed toward immature than adult heterospecifics. Primates were the initiators in most interactions. These findings offer new insights into the diversity and contexts of heterospecific sociality in primates and suggest that some behavioral tendencies relevant to later forms of human–animal companionship – such as caregiving, tolerance, and exploratory play – may be more widespread among primates than previously recognized.

Correction: Identifying remnant biodiversity hotspots in Southern Asia reveals disequilibrium in mammalian communities - Caroline Charão Sartor; Zaneta Kaszta; Jan Kamler; Andrew J. Hearn; Eric Ash; Gilmoore Bolongon; Özgün Emre Can; Phan Channa; Susan Cheyne; Amy Fitzmaurice; Iding Achmad Haidir; Pyae Phyoe Kyaw; et al. (Biodiversity and Conservation, 2025)

Identifying gaps in the conservation of small wild cats of Southeast Asia - Luca Chiaverini; David W. Macdonald; Andrew J. Hearn; Żaneta Kaszta; Eric Ash; Özgün Emre Can; Phan Channa; Susan M. Cheyne; Gopalasamy Reuben Clements; Iding Achmad Haidir; Jan F. Kamler; Pyae Phyoe Kyaw; et al. (Biodiversity and Conservation, 2025)
Southeast Asia hosts more felid species than any other region and, although smaller (

Identifying remnant biodiversity hotspots in Southern Asia reveals disequilibrium in mammalian communities - Caroline Charão Sartor; Zaneta Kaszta; Jan Kamler; Andrew J. Hearn; Eric Ash; Gilmoore Bolongon; Özgün Emre Can; Phan Channa; Susan Cheyne; Amy Fitzmaurice; Iding Achmad Haidir; Pyae Phyoe Kyaw; et al. (Biodiversity and Conservation, 2024)
Identification of highly biodiverse areas has become a crucial step in protecting species richness, especially considering the rapid collapse of biodiversity and the limited funds available to avert, far less to reverse, these trends. Therefore, we aimed to identify the most important areas for the conservation of specified mammalian groups in Southern Asia, a region rich in biodiversity hotspots threatened by increasing rates of habitat loss and other anthropogenic activities. To achieve this, we modelled the occupancy of ungulates and of small, medium and large carnivorans at 20 study sites across the region and identified hotspots of species richness. We analysed the variation of estimated space use between different species groups and ranked areas according to their predicted importance for mammalian species conservation. Our results reveal a significant positive correlation in the spatial utilization patterns of competitive carnivores, yet no correlation among carnivores and their prey species, suggesting that anthropogenic impacts in the region are constraining species to coexist in only the few remaining suitable areas, superseding interactions between species guilds. Although the rank of site importance varied amongst species groups, we were able to identify a consensus on sites that are crucial for the conservation of all groups considered. Most of these top-ranking sites were located in the peninsular region of Thailand. We argue that, of the areas assessed, these sites represent the most important refuges for species conservation in the region, and their protection is critical for the maintenance of the biodiversity in Southern Asia.

Confirmation of Skywalker Hoolock Gibbon (Hoolock tianxing) in Myanmar Extends Known Geographic Range of an Endangered Primate - Pyae Phyo Aung; Ngwe Lwin; Tin Htun Aung; Thura Soe Min Htike; Carolyn Thompson; Christian Roos; Sa Myo Zaw; L. Zawng Lum; Win Naing Oo; Zung Sau; Samuel T. Turvey; Wai Zinn Thein; et al. (International Journal of Primatology, 2024)
Characterizing genetically distinct populations of primates is important for protecting biodiversity and effectively allocating conservation resources. Skywalker gibbons ( Hoolock tianxing ) were first described in 2017, with the only confirmed population consisting of 150 individuals in Mt. Gaoligong, Yunnan Province, China. Based on river geography, the distribution of the skywalker gibbon has been hypothesized to extend into Myanmar between the N’Mai Kha and Ayeyarwaddy Rivers to the west, and the Salween River (named the Thanlwin River in Myanmar and Nujiang River in China) to the east. We conducted acoustic point-count sampling surveys, collected noninvasive samples for molecular mitochondrial cytochrome b gene identification, and took photographs for morphological identification at six sites in Kachin State and three sites in Shan State to determine the presence of skywalker gibbons in predicted suitable forest areas in Myanmar. We also conducted 50 semistructured interviews with members of communities surrounding gibbon range forests to understand potential threats. In Kachin State, we audio-recorded 23 gibbon groups with group densities ranging between 0.57 and 3.6 group/km 2 . In Shan State, we audio-recorded 21 gibbon groups with group densities ranging between 0.134 and 1.0 group/km 2 . Based on genetic data obtained from skin and saliva samples, the gibbons were identified as skywalker gibbons (99.54–100% identity). Although these findings increase the species’ known population size and confirmed distribution, skywalker gibbons in Myanmar are threatened by local habitat loss, degradation, and fragmentation. Most of the skywalker gibbon population in Myanmar exists outside protected areas. Therefore, the IUCN Red List status of the skywalker gibbon should remain as Endangered.

Implications of large-scale infrastructure development for biodiversity in Indonesian Borneo - Katie L. Spencer; Nicolas J. Deere; Muhammad Aini; Ryan Avriandy; Gail Campbell-Smith; Susan M. Cheyne; David L.A. Gaveau; Tatyana Humle; Joseph Hutabarat; Brent Loken; David W. Macdonald; Andrew J. Marshall; et al. (Science of The Total Environment, 2023)

Influences of Forest Structure on the Density and Habitat Preference of Two Sympatric Gibbons (Symphalangus syndactylus and Hylobates lar) - Emma L. Hankinson; Ross A. Hill; Christopher D. Marsh; Matt G. Nowak; Abdullah Abdullah; Nursahara Pasaribu; Supriadi; Vincent Nijman; Susan M. Cheyne; Amanda H. Korstjens (International Journal of Primatology, 2021)

Being “Out” in the Field: Who Is Responsible for Health and Safety? - Susan M. Cheyne (International Journal of Primatology, 2019)

Correction to: Down from the treetops: red langur (Presbytis rubicunda) terrestrial behavior - Susan M. Cheyne; Supiansyah; Adul; Claire J. Neale; Carolyn Thompson; Cara H. Wilcox; Yvette C. Ehlers Smith; David A. Ehlers Smith (Primates, 2018)

Down from the treetops: red langur (Presbytis rubicunda) terrestrial behavior - Susan M. Cheyne; Supiansyah; Adul; Claire J. Neale; Carolyn Thompson; Cara H. Wilcox; Yvette C. Ehlers Smith; David A. Ehlers Smith (Primates, 2018)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

A Comparison of Hylobatid Survey Methods Using Triangulation on Müller’s Gibbon (Hylobates muelleri) in Sungai Wain Protection Forest, East Kalimantan, Indonesia - Lauren J. Gilhooly; Yaya Rayadin; Susan M. Cheyne (International Journal of Primatology, 2015)

Interactions between a wild Bornean orang-utan and a Philippine slow loris in a peat-swamp forest - Helen C. Morrogh-Bernard; Jessica M. Stitt; Zeri Yeen; K. A. I. Nekaris; Susan M. Cheyne (Primates, 2014)

Home-Range Use and Activity Patterns of the Red Langur (Presbytis rubicunda) in Sabangau Tropical Peat-Swamp Forest, Central Kalimantan, Indonesian Borneo - David A. Ehlers Smith; Yvette C. Ehlers Smith; Susan M. Cheyne (International Journal of Primatology, 2013)

Note-, phrase- and song-specific acoustic variables contributing to the individuality of male duet song in the Bornean southern gibbon (Hylobates albibarbis) - Klara M. Wanelik; Abdul Azis; Susan M. Cheyne (Primates, 2013)

Line Transect and Triangulation Surveys Provide Reliable Estimates of the Density of Kloss’ Gibbons (Hylobates klossii) on Siberut Island, Indonesia - Andrea Höing; Marcel C. Quinten; Yohana Maria Indrawati; Susan M. Cheyne; Matthias Waltert (International Journal of Primatology, 2013)
Estimating population densities of key species is crucial for many conservation programs. Density estimates provide baseline data and enable monitoring of population size. Several different survey methods are available, and the choice of method depends on the species and study aims. Few studies have compared the accuracy and efficiency of different survey methods for large mammals, particularly for primates. Here we compare estimates of density and abundance of Kloss’ gibbons ( Hylobates klossii ) using two of the most common survey methods: line transect distance sampling and triangulation. Line transect surveys (survey effort: 155.5 km) produced a total of 101 auditory and visual encounters and a density estimate of 5.5 gibbon clusters (groups or subgroups of primate social units)/km 2 . Triangulation conducted from 12 listening posts during the same period revealed a similar density estimate of 5.0 clusters/km 2 . Coefficients of variation of cluster density estimates were slightly higher from triangulation (0.24) than from line transects (0.17), resulting in a lack of precision in detecting changes in cluster densities of <66 % for triangulation and <47 % for line transect surveys at the 5 % significance level with a statistical power of 50 %. This case study shows that both methods may provide estimates with similar accuracy but that line transects can result in more precise estimates and allow assessment of other primate species. For a rapid assessment of gibbon density under time and financial constraints, the triangulation method also may be appropriate.

Biology and behaviour of reintroduced gibbons - Susan M. Cheyne; David J. Chivers; Jito Sugardjito (Biodiversity and Conservation, 2008)

Density and population estimate of gibbons (Hylobates albibarbis) in the Sabangau catchment, Central Kalimantan, Indonesia - Susan M. Cheyne; Claire J. H. Thompson; Abigail C. Phillips; Robyn M. C. Hill; Suwido H. Limin (Primates, 2008)

Unusual behaviour of captive-raised gibbons: implications for welfare - Susan M. Cheyne (Primates, 2007)

Unusual behaviour of captive-raised gibbons: implications for welfare - Susan M. Cheyne (Primates, 2006)